Integration of IoT Devices in PAI Learning: Strategic Impact on Curriculum Management, Evaluation, and Resources - Titi Hendrawati (LP. Ma'arif Janggan Magetan, 2025)
This research discusses the ongoing challenges in Islamic Religious Education (PAI) learning at STAI Haji Agus Salim, specifically the mismatch between lecturers' teaching styles, limited facilities, and student characteristics. This research emphasizes the role of the Internet of Things (IoT) as a strategic tool for improving the quality of education and learning management. Using a qualitative design through phenomenological analysis involving interviews, observations, and document review, the research findings indicate that IoT can support adaptive learning, real-time assessment, and managerial effectiveness. This integration aligns with Vygotsky's constructivist scaffolding theory and the TPACK framework in supporting teachers' digital literacy. However, there are still challenges related to technological competence, protection of student data, and resistance to organizational culture change. This research concludes that IoT has the potential to drive the creation of an adaptive, inclusive, and sustainable smart campus ecosystem, and that a phased implementation in a curriculum tracking system with TPACK-based training can be considered.